Rancang Bangun Sistem Monitoring Listrik Tiga Fasa Berbasis Wireless Sensor Network Menggunakan LoRa Ra-02 SX1278 - Pratama, Aditya; Amrita, A. A. Ngurah; Khrisne, Duman Care (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
Electricity monitoring is making to determine the quality of electricity used. Currently, electricity monitoring is still done manually together with it requires a system that can measure the electrical parameters automatically. Therefore, an electrical monitoring system is designed for a three-phase system based on a wireless sensor network (WSN) using LoRa communication. The system consists of a transmitter node as a measured voltage, current, frequency, power factor, and active power using the PZEM-004T module. The receiver node is a gateway that receives data from the transmitter node used LoRa transmission and then forwards the data to be stored in a database using the internet network. The receiver node is equipped with backup data when the node receiver cannot be connected to the internet network. Finally, web monitoring is designed to make it easier for users to access electricity monitoring data online. Web monitoring will display data onto voltage, current, frequency, power factor in a single-phase system and active power in the form of the three-phase system into tables and graphs.